Highly selective n-butanol gas sensor based on porous In2O3 nanoparticles prepared by solvothermal treatment. (15th August 2018) - Wang, Jian; Zheng, Zhi; An, Dongmin; Tong, Xiaoqiang; Zhou, Qingjun
Abstract: Porous In2 O3 nanoparticles with sizes ranging from 20 to 50 nm were successfully prepared using a solvothermal method. The phase structure and morphology of the In2 O3 samples were characterized using X-ray powder diffraction and scanning electron microscopy, respectively. Brunauer-Emmett-Teller analysis revealed that the obtained optimal In2 O3 nanoparticles were porous with a large surface area of 108.77 m 2 /g. Incorporated into a ceramic tube gas sensor, the In2 O3 nanoparticles acted as a gas-sensing material for n-butanol. The sensor performed well, including a high response, short response and recovery times, good selectivity, and good reproducibility and stability to n-butanol gas at a working temperature of 140 °C. These porous In2 O3 nanoparticles thus show potential for use as gas-sensing materials to monitor the concentration of n-butanol gas.